ELK3-CXCL16 axis determines natural killer cell cytotoxicity via the chemotactic activity of CXCL16 in triple negative breast cancer - Hae-Yun Jung; Dae-Keum Lee; Minwook Lee; Seung Hee Choi; Joo Dong Park; Eun-Su Ko; Jongwon Lee; Kyung-Soon Park; Hae-Yun Jung (OncoImmunology)
Triple-negative breast cancer (TNBC) is the most challenging subtype of breast cancer because of its aggressive behavior and the limited therapeutic strategies available. In the last decade, immunotherapy has become a promising treatment to prolong survival in advanced solid cancers including TNBC. However, the efficacy of immunotherapy in solid cancers remains limited because solid tumors contain few tumor-infiltrating lymphocytes. Here, we show that targeting an ETS transcription factor ELK3 (ELK3) recruits immune cells including natural killer (NK) cells into tumors via the chemotactic activity of chemokine. ELK3 depletion increases CXCL16 expression level and promotes NK cell cytotoxicity through CXCL16-mediated NK cell recruitment in TNBC. In silico analysis showed that ELK3 is negatively correlated with CXCL16 expression in breast cancer patient samples. Low expression of ELK3 and high expression of CXCL16 were associated with a better prognosis. Low expression of ELK3 and high expression of CXCL16 were associated with increased expression of NK cell-related genes. Our findings demonstrate that the ELK3-CXCL16 axis modulates NK cell recruitment to increase NK cell cytotoxicity, suggesting that targeting the ELK3 gene could be an adjuvant strategy for increasing the efficacy of immunotherapy in TNBC.